Pengaruh Family Ritual Vacation dan Financial Management Terhadap Wellbeing pada Orang Tua yang Memiliki Anak yang Sedang Menempuh Pendidikan - Lius, Vicktor Hugo; Sanjaya, Ersa Lanang (Psychopreneur Journal, 2020)
In parents with their kids participating in education, there is some problems they faces. Financial sacrifices and risks of conflict also facility problems when doing family vacation is some problem they have to face. This study will explore more about influence of family ritual vacation and financial management to wellbeing in parents with their kids participating in education. Quantitative research methods with regression analysis technique are used in this study, conducting around 91 participants. Results of the study concludes that there is significant influence between financial management to wellbeing (p<0,05), but not true for family ritual vacation to wellbeing (p=0,125). This finding implied higher ability to plan financial management, their wellbeing will be also higher and vice versa. But the case isn’t true for family ritual vacation as the influence are insignificant.